The effect of parenting type on anxiety level of hospitalised children: A cross-sectional study - Juli Widiyanto; Hasambua; Yeni Yarnita (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the influence of parenting type on the anxiety level of hospitalised children. Method: The cross-sectional, observational study was conducted in June 2021 at the paediatric ward of Arifin Ahmad General Hospital, Pekanbaru, Riau, Indonesia, and comprised inpatients and their parents. The Data analyses was performed with SPSS 16.0. Statistical test results were considered significant at a p <0.05 level when 95% confidence intervals did not include zero. A personal Chi-Square test was applied to determine the influence of parenting type on the anxiety level of hospitalised children. Results: There were 25 children with mean age 4.04±4.84 years, while the mean age of 25 parents was 34.87±36.89 years. Among the parents, 15(60%) were mothers. A significant influence was found between the type of parenting and the anxiety levels in hospitalised children (p=0.037; odds ratio:2.750; 95% confidence interval: 1.33-18.89). Conclusion: Good parenting patterns during treatment could reduce anxiety levels in hospitalised children. Keywords: Odds Ratio, Anxiety, Sadness, Emotions, Anger, Confidence, Parenting.